Analisis Harmonisasi Standar Akuntansi Syariah dengan Prinsip Syariah untuk Memperkuat Transparansi Pelaporan Keuangan Modern - Nuraini Nuraini; Siska Asriana; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study analyzes the harmonization of Islamic accounting standards with Sharia principles in strengthening the transparency of modern financial reporting. The discussion integrates conceptual analysis, empirical evidence from prior studies, and insights drawn from official regulatory and industry reports. The findings show that differences between IFRS and AAOIFI, particularly in recognition, measurement, and disclosure, have significant implications for transparency and comparability. Harmonization supported by strong Sharia governance improves reporting quality, limits earnings management, and enhances ethical accountability. Official reports further confirm that institutions adopting a balanced integration of global standards and Sharia-based guidelines demonstrate more credible financial information, better risk disclosure, and stronger public trust. The study highlights that harmonization is not merely a technical alignment but an institutional and normative process that connects global financial practices with Islamic values. This integration reinforces the role of financial reporting as a tool of accountability, sustainability, and legitimacy in the contemporary Islamic financial system.